Characterization of an Unusually Aggressive Ovarian Malignant Sex Cord Stromal Tumor in an Adolescent Female With Peutz-Jeghers Syndrome. (11th September 2019) - Benzi, Eduardo; Patil, Ninad
Abstract: Peutz-Jeghers syndrome (PJS) is a rare autosomal dominant disorder with mutations in SKT11 (19p13.3), mucocutaneous hyperpigmentation, gastrointestinal hamartomatous polyposis, and increased cancer predisposition. A PJS-associated distinctive ovarian tumor is sex cord tumor with annular tubules (SCTAT), which is multifocal, microscopic, bilateral, and almost always clinically benign. Non-SCTAT ovarian tumors with malignant behavior are exceptionally rare. We describe a malignant, multiply recurrent, widely metastatic sex cord stromal tumor in PJS. Case Report: A 17-year-old female presented with new complaints of unintentional weight loss, alopecia, and abdominal fullness. She had a PJS diagnosis at age 7 with mucocutaneous pigmentation, gastrointestinal polyposis, and STK11 mutation. CT showed a 23-cm abdominopelvic mass with diffuse peritoneal metastases and malignant pleural effusion. CA-125 was elevated. CEA, CA 19-9, β-hCG, AFP, and LDH were normal. Laparoscopic biopsy pathology revealed a tumor composed of sheets and loose aggregates of mitotic spindled and round heterogenous eosinophilic and basophilic cells within fibromyxoid stroma. Rare tubules with eosinophilic cytoplasm and focal foamy cells were also seen. IHC was significant for inhibin, calretinin, CD56 and WT1 positivity, and cytokeratin and EMA negativity, consistent with poorly differentiated sex cord stromal tumor. Interestingly, EM showed neurosecretory dense core granules and neurite-like processes. After neoadjuvant therapy, the resected left adnexal mass was 25.5 cm, purple-gray/tan-red, heterogeneous, diffusely cystic, diffusely edematous, rubbery to spongy. In the left ovary were also found unassociated microscopic SCTAT foci. During adjuvant chemotherapy, the patient became pregnant. During the pregnancy, the patient developed liver and pelvic peritoneal recurrence and continued altered chemotherapy. She delivered a healthy late-preterm infant but also concurrently had diffuse peritoneal recurrence. She underwent two more cycles of adjuvant chemotherapy. Approximately 2 years after finishing adjuvant chemotherapy, she again developed peritoneal recurrences, which were resected, and partial chemotherapy response was seen on pathology. She is currently undergoing additional chemotherapy cycles 4 years since the initial diagnosis.